PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA - ., Rayana; Rhamayanti, Yuni; Harahap, Adek Nilasari (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
The aim of this research is to determine the effect of the discovery learning model on the mathematics learning outcomes of class VIII students at SMP Negeri 1 Marancar, Algebra Operations Material. This type of research is quasi-experimental research. The research population was all students of class VIII odd semester of SMP Negeri 1 Marancar TP. 2023/2024 which consists of 2 classrooms totaling 42 class VIII students. The control class is class VIII-1 and the experimental class is class VIII-2. The normality test value for the control class is 0.038˃0.05, meaning it is normally distributed. Then for the experimental (treatment) class, the calculated L value was 0.392 ˃ 0.05, meaning it was normally distributed. So it can be concluded that the data distribution in this study is normally distributed. Meanwhile, the homogeneity result is a significance value of 0.209˃0.05. This means that it can be concluded that the data distribution for the control class and experimental class has homogeneous data conditions. Furthermore, the tests carried out showed that there was an influence of the discovery learning model on the mathematics learning outcomes of class VIII students at SMP Negeri 1 Marancar. Based on this table, the Sig value can be seen. (2-Tailed) is 0.894˃ of 0.05. So Ho is rejected and Ha is accepted. This means that there is an influence of the discovery learning model on the mathematics learning outcomes of class VIII students at SMP Negeri 1 Marancar. Keywords— Discovery Learning, Learning Outcomes, Algebra